Investigation of long-range transport and chemical fate of organophosphate esters (OPEs) in the marine environment - Li, Jing (Staats- und Universitätsbibliothek Hamburg Carl von Ossietzky, 2019)
Organophosphate esters (OPEs) are a group of man-made industrial chemicals that have been widely applied in many industrial processes and household products. The use of OPEs throughout the world has drastically increased partly because these chemicals have been proposed as alternatives for brominated flame retardants (BFRs). Most OPEs are applied as additive materials on the surface of products, which allows these chemicals to easily spread into the environment by volatilization, leaching, and abrasion. To identify and evaluate the OPE fingerprints in the marine environment and the long-range transport (LRT) potential, occurrences of OPEs in the North Atlantic Ocean, the Arctic Ocean as well as the Bohai and Yellow Seas (China) have been investigated in this study. For a more holistic view of OPEs in the environment, different models have been used in combination with experimental data, including air-seawater exchange, gas-particle partitioning and LRT models. This study has been designed to improve our understanding of the OPE interactions between land, atmosphere, and oceans, the source-to-concentration relationships and the contributions of OPE source regions to polar areas. Due to political regulations, the produced substance amounts and compound patterns change over time in a given region. At the same time, production capacities are relocated to less regulated regions. As a result, different OPE occurrence patterns are observed in Europe and East Asia. This study also highlighted that OPEs are subject to LRT via both air and seawater from the European continent and seas to the North Atlantic and Arctic regions. A net deposition occurs over the North Atlantic and Arctic oceans based on the air-sea exchange fluxes calculated by the two-film resistance model. The gas-particle partitioning analysis based on the samples collected from the Bohai and Yellow Seas suggests that OPEs have a low potential to achieve equilibrium or are sensitive to the artificial sampling method. This study also seeks to characterize ...